Don't become a burden and don't complain: a case study of older persons suffering from incurable cancer and living alone in rural areas - Guri Bitnes Wiik; Siri Devik; Ove Hellzen (MDPI AG, 2011)
The majority of older people wish to continue to live at home for as long as possible. As a consequence, the healthcare system, including cancer care, is located in urban areas and people living in rural areas must commute to gain access to the services offered. The aim of this study was to investigate how older people, who live on their own, experience living with incurable cancer and commuting for palliative care in rural Norway. A case study was designed and informants were recruited not because they were typical but because they were deemed to have the potential to contribute to knowledge about the phenomenon of being an older person who has been diagnosed with incurable cancer and lives alone in a rural area. Three major categories were identified: “Hovering between hope and fear, Stressful commuting to palliative care, and Being exhausted. The findings indicated that older people who have been stricken with incurable cancer and who live alone in rural areas have to walk the palliative path alone. A common feature of all the informants is that they do not speak out and they do not complain. Even though the trend in healthcare is towards centralized treatment, shorter and more effective stays in hospital, and policlinic (policlinic services are a place where healthcare services can be accessed without the need for an overnight stay in hospital, usually such clinics are located close to a hospital) treatment and care, not all older persons manage to take care of themselves. The findings suggest that nurses should pay more attention to these patients’ needs for care at different levels of the healthcare service.